Apoptotic effect of a phytosterol-ingredient and its main phytosterol (β-sitosterol) in human cancer cell lines. (3rd April 2019) - Alvarez-Sala, Andrea; Attanzio, Alessandro; Tesoriere, Luisa; Garcia-Llatas, Guadalupe; Barberá, Reyes; Cilla, Antonio
Abstract: Dietary interventions may effectively control cancer development, with phytosterols (PS) being a class of cancer chemopreventive dietary phytochemicals. The present study, for the first time, evaluates the antiproliferative effects of a PS-ingredient used for the enrichment of several foods and its main PS, β-sitosterol, at physiological serum levels, in the most prevalent cancer cells in women (breast (MCF-7), colon (HCT116) and cervical (HeLa)). In all three cell lines, these compounds induced significant cell viability reduction without a clear time- and dose-dependent response. Moreover, all treatments produced apoptotic cell death with the induction of DNA fragmentation through the appearance of a sub-G1 cell population. Thus, the use of PS as functional ingredients in the development of PS-enriched foods could exert a potential preventive effect against human breast, colon and cervical cancer, although further in vivo studies are required to confirm our preclinical findings.